2020
DOI: 10.3386/w27018
|View full text |Cite
|
Sign up to set email alerts
|

Lock-downs, Loneliness and Life Satisfaction

Abstract: I thank the University of Minnesota Population Center IPUMS for the ATUS-X extracts and Jeff Biddle, George Borjas, Katie Genadek and Andrew Oswald for helpful comments. No funding was received for this research. The views expressed herein are those of the author and do not necessarily reflect the views of the National Bureau of Economic Research. NBER working papers are circulated for discussion and comment purposes. They have not been peer-reviewed or been subject to the review by the NBER Board of Directors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 12 publications
(6 reference statements)
0
24
1
Order By: Relevance
“…Co-residency with family members may decrease loneliness but may also increase intrafamily conflicts and the burden of taking care of others (Ren and Treiman 2015). We observe a significant and positive association between marriage and mental distress, which is contradictory to prior studies (Hamermesh 2020). This may because the majority of unmarried people (61 percent) in our sample are college students who are less likely to worry about income loss or supporting their families than their married and less educated counterparts.…”
Section: Empirical Findingscontrasting
confidence: 99%
See 1 more Smart Citation
“…Co-residency with family members may decrease loneliness but may also increase intrafamily conflicts and the burden of taking care of others (Ren and Treiman 2015). We observe a significant and positive association between marriage and mental distress, which is contradictory to prior studies (Hamermesh 2020). This may because the majority of unmarried people (61 percent) in our sample are college students who are less likely to worry about income loss or supporting their families than their married and less educated counterparts.…”
Section: Empirical Findingscontrasting
confidence: 99%
“…These large-scale quarantine and social-distancing restrictions slowed the increase in new COVID-19 cases and later became a model for other provinces in China and countries that were attempting to stop the spread of COVID-19 (Chen et al 2020). Extensive attention has been paid to the implications of such lockdowns and quarantines on individuals' well-being (Hamermesh 2020;Holmes et al 2020;Rajkumar 2020). Scholars have revealed that quarantine and physical-distancing measures are associated with worsened mental health, and highlighted contributing roles of uncertainty, the seriousness of COVID-19, misinformation, and social isolation (Rajkumar 2020;Yang et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…But we also note that there were substantial economic costs of this intervention. In addition to substantial utility losses caused by social distancing from nonhousehold members (Hamermesh 2020), the SIPO was accompanied by substantial job loss.…”
Section: Discussionmentioning
confidence: 99%
“…buildbackbetteruk.org). To date, there are few studies that assess the psychological impacts of Covid-19 (Brodeur et al 2020;Greyling et al 2020;Hamermesh 2020). Recently, the preliminary results from another survey in Luxembourg were released, which also includes France, Germany, Italy, Spain and Sweden (Vögele et al 2020).…”
Section: Discussionmentioning
confidence: 99%